Research on Ottosen constitutive model of frozen soil under impact load. (January 2021) - Zhu, Zhiwu; Fu, Tiantian; Zhou, Zhiwei; Cao, Chenxu
Abstract: Impact blasting loading is an unavoidable problem in cold area construction. In this study, the dynamic characteristics of frozen soil with a water content of 20% and different freezing temperatures are studied under the impact of a spilt Hopkinson pressure bar. Two aspects of the dynamic mechanical response are analyzed to describe the experimental results: temperature rises and the failure mechanism. A rate damage equation is derived considering the improved Ottosen model and thermal activation theory. The experimental results indicate that the improved nonlinear model can be applied to understand the impact mechanics of frozen soil and predict the evolution law of typical mechanical indexes. Highlights: Frozen soil is a rate-dependent and temperature-sensitive material. A damage constitutive model of frozen soil is established. The strain rate enhancement term is introduced into the model. The strain rate and temperature affect the impact ultimate failure form of frozen soil. The theoretical results match well with the experimental ones.